2015
DOI: 10.1007/s00264-015-2886-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of discogenic back pain with autologous bone marrow concentrate injection with minimum two year follow-up

Abstract: This study provides evidence of safety and feasibility in the non-surgical treatment of discogenic pain with autologous BMC, with durable pain relief (71 % VAS reduction) and ODI improvements (> 64 %) through two years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 30 publications
1
113
0
Order By: Relevance
“…Several studies have demonstrated improvement in clinical scores including ODI, VAS, and JOA beginning 1 month post-PRP injection [64][65][66][67]. Additionally, these studies have reported no complications associated with MSC and PRP injections [64].…”
Section: Treatment Non-operativementioning
confidence: 96%
“…Several studies have demonstrated improvement in clinical scores including ODI, VAS, and JOA beginning 1 month post-PRP injection [64][65][66][67]. Additionally, these studies have reported no complications associated with MSC and PRP injections [64].…”
Section: Treatment Non-operativementioning
confidence: 96%
“…The study by Pettine et al, though it only included 26 subjects, demonstrated promising results (71 % reduction in VAS and [64 % improvement in ODI at 2 years) of BMC injection into one or two level degenerative discs in chronic LBP patients who had failed conservative treatment [17]. This study demonstrated that BMC injection can potentially provide long term relief (approximately 80 % avoided surgery at 2 years).…”
Section: Discussionmentioning
confidence: 55%
“…A recent study by Pettine et al evaluated 26 patients with chronic LBP after intradiscal injection of autologous BMC and performed follow-up from 3 months to 2 years post-injection [17]. The results demonstrated significant improvements in both ODI and VAS at one and 2 years.…”
Section: Injection Proceduresmentioning
confidence: 88%
See 1 more Smart Citation
“…Early clinical studies for intradiscal injection of autologous bone marrow aspirate for discogenic back pain have been positive. Clinical follow up at 2 years after autologous bone marrow concentrate injection showed that 40% had improvement on MRI, while none had worse appearing MRI67 . Autologous bone marrow concentrate has been shown to significantly decrease lumbar discogenic pain, and that pain relief was improved at higher cell injection concentrations68 .…”
mentioning
confidence: 94%